KONJUNGSI KOORDINATIF BAHASA FLORES - Safitri, Reski Ummi; Sinaga, Mangatur; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is aim of analyze form and function conjunctions coordination language flores. Methods used in this research is the qualitative study. Technique data collection in this research is a technique interview. Technique data analysis done in this research is to collect data of said hyphen in language flores, identify the types of word relations in tuturan language flores, analyze form and function conjunctions coordination in language flores .Based on the discussion th , can be concluded that in this research found the form of a conjunction coordination about 56 of data. The coordinating conjunction function, there are 9 functions namely the sum function of 2 conjunctions, the coordinating conjunction no'on there are 3 data and the coordinating conjunction functions there are 3 data, the function of selecting 1 conjunction, there are 4 data le, there are 4 conflicting functions, but there are 5 data and there are 1 data kuu, rectification function with 1 conjunction, frozen there is 1 data, 2 conjunction affirmation functions, I have 3 data and I have 4 data, 2 conjunction limitation functions, if there are 2 data and sedde there are 3 data, sorting function 3 conjunction, there is 1 data, there is only 1 data and there are 3 data nioh, the equalization function 2 conjunction we have 9 data and let us have 2 data and the inference function 3 coordinate conjunction newewe there are 3 data, neti have 5 data and there are no data 1 data. Key Words: Conjunction, Coordinative, Flores